Pemberdayaan Gerakan Masyarakat 4G (Go Green, Go Health, Go Clean dan Go Smart) di UPTD Puskesmas Tangkiling - Elsa Trinovita; Dewi Klarita Furtuna; Silvani Permatasari; Astri Widiarti; Galih Indra Permana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Indonesia is one of the countries set as a corona disaster emergency with the increasing Covid-19 case. One of the factors that caused an increase in Covid-19 cases was the lack of public awareness in implementing 5-M prevention behavior using masks, hand washing using soap and running water, keeping distance, staying away from the crowd, and limiting mobilization and interaction) in his daily life can be a risk transmission in society. Therefore, an approach was carried out in increasing public awareness of the new normal adaptation in the face of the Covid-19 pandemic condition by promoting the "4G Movement" (Go Green, Go Health, Go Clean and Go Smart) at the UPTD Puskesmas Tangkililing carried out by the Faculty Team Medicine of Palangka Raya University. This activity aims to increase public awareness and understanding of the importance of good health behavior by applying a strict health protocol in the condition of the Covid-19 pandemic as a step in supporting government programs and maintaining personal, family, and community health in anticipation of the spread of Covid-19. It implements this activity in the form of a lecture/socialization, demonstration, free pocket book distribution, and educational video playback in animation. This activity runs smoothly and occurs interactive dialogue with respondents in the UPTD Puskemas environment. The 4G movement is one of the programs that contribute positively and can be applied by the community in increasing compliance in implementing a health protocol.